Arthritis as a risk factor for carpal tunnel syndrome: a meta-analysis. (2nd September 2016) - Shiri, R
Abstract : Objectives : The effects of inflammatory and degenerative arthritis on carpal tunnel syndrome (CTS) are not well known. This systematic review and meta-analysis aimed to assess whether rheumatoid arthritis (RA) and osteoarthritis (OA) increase the risk of CTS. Method : Literature searches were conducted in PubMed, Embase, Web of Science, Scopus, Google Scholar, and ResearchGate until January 2015. Twenty-three (five cohort, 10 case control, and eight cross sectional) studies qualified for the meta-analyses. A random-effects meta-analysis was used and heterogeneity and publication bias were assessed. Results : Both RA and OA were associated with CTS. Pooled unadjusted odds ratios (ORs) were 1.91 [95% confidence interval (CI) 1.33–2.75, I 2 = 55.2%, nine studies, n = 10 688] for arthritis (either inflammatory or degenerative), 2.91 (95% CI 2.33–3.62, I 2 = 22.3%, 11 studies, n = 74 730) for RA, and 2.13 (95% CI 1.65–2.76, I 2 = 39.2%, five studies, n = 20 574) for OA of any joint. Pooled confounder-adjusted ORs were 1.96 (95% CI 1.21–3.18, I 2 = 73.1%, six studies, n = 11 542) for arthritis, 1.96 (95% CI 1.57–2.44, I 2 = 32.2%, eight studies, n = 72 212) for RA, and 1.87 (95% CI 1.64–2.13, I 2 = 0%, two studies, n = 19 480) for OA. There was no evidence of publication bias, and excluding cross-sectional studies or studies appraised as having a high risk of selection bias did not change the magnitude of the associations. Conclusions : The findings of this systematic review and meta-analysis suggest that both RA and OA increase the risk of CTS. Further prospective studies on the effect of wrist OA on CTS are needed.